Improved method for measuring vitamin B(12) in serum using intrinsic factor, (57)CoB(12), and coated charcoal - Raven, J. L. (1969)
An improved and simplified method is described for the measurement of vitamin B(12) in serum using intrinsic factor, (57)CoB(12), and coated charcoal. The extraction of serum in the presence of cyanide and the incorporation of B(12)-deficient serum into the intrinsic factor control has increased the accuracy of the method for both sera and crystalline B(12) solutions. There are interesting differences between the results obtained for some sera by the isotope and L. leichmannii methods and the reasons for these differences are discussed.